1987
DOI: 10.1016/0076-6879(87)43090-5
|View full text |Cite
|
Sign up to set email alerts
|

ω-Amino acid-pyruvate aminotransferase

Abstract: Succinic semialdehyde -FL-Glutamate 13-alanine transaminase is characterized by its requirement for pyruvate and r-aminobutyrate transaminase for a-ketoglutarate as an amino acceptor. With the latter enzyme, many studies have been carried out using mammalian enzyme with an emphasis on its physiological function.8-10) Some of them were purified to homogeneity and partially characterized. There are another (0-amino acid transaminase catalyzing transamination of co-amino group of a, w-diaminocarboxylic acid such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…When an w-TA capable of deaminating (S)-α-methylbenzylamine ((S)-α-MBA) was first reported as a research paper (Shin and Kim 1997), the 5-TA was expected to be a variant of 5-amino acid:pyruvate transaminase (5-APT) (EC 2.6.1.18) because 5-APT was the only 5-TA at that time that was known to deaminate amine compounds (Yonaha et al 1987). However, it turned out that the newly found 5-TA was very different from 5-APT, because the 5-TA could not deaminate β-alanine which is a typical amino donor of 5-APT (Shin and Kim 2002).…”
Section: Enzyme Nomenclaturementioning
confidence: 98%
“…When an w-TA capable of deaminating (S)-α-methylbenzylamine ((S)-α-MBA) was first reported as a research paper (Shin and Kim 1997), the 5-TA was expected to be a variant of 5-amino acid:pyruvate transaminase (5-APT) (EC 2.6.1.18) because 5-APT was the only 5-TA at that time that was known to deaminate amine compounds (Yonaha et al 1987). However, it turned out that the newly found 5-TA was very different from 5-APT, because the 5-TA could not deaminate β-alanine which is a typical amino donor of 5-APT (Shin and Kim 2002).…”
Section: Enzyme Nomenclaturementioning
confidence: 98%
“…To prepare the crude extract, the harvested cells (10 g of cell wet weight) of A. denitrificans Y2k-2 were suspended in 20 ml of sonication buffer, which contains 20 M PLP, 0.2 mM EDTA, 1.0 mM phenylmethylsulfonyl fluoride (PMSF), and 0.01% (wt/wt) 2-mercaptoethanol in 10 mM phosphate buffer (pH 7.0), and disrupted by sonication at 4°C. It was strongly inhibited by 5 mM 3-amino-2,3-dihydrobenzoic acid (gabaculine), hydroxylamine, or aminooxyacetic acid (25), and equivalent amounts of L-alanine were produced according to the consumed pyruvate. The enzyme involved in the kinetic resolution was confirmed to be an -amino acid:pyruvate transaminase (-APT).…”
mentioning
confidence: 99%
“…However, none of these proteins has been biochemically characterized yet. AptA had 45% identity to -APT from Pseudomonas putida, which is the only well-characterized enzyme (25,26). The linear alignment of AptA and the six related proteins mentioned above showed that these enzymes are highly homologous to each other (Fig.…”
mentioning
confidence: 99%
“…Among the TAs, only -TA has been reported to show catalytic activity towards primary amines (6,21). Therefore, the chemical properties of the starting amino donor and acceptor substrates in the -TA reaction are often different from those of the resulting products.…”
mentioning
confidence: 99%
“…TAs can be classified as ␣-or -TA according to the position of the amino group transferred with respect to the carboxyl group of the substrate (8,9,21). Among the TAs, only -TA has been reported to show catalytic activity towards primary amines (6,21).…”
mentioning
confidence: 99%